Determinación de plomo en aguas de la bocamina pampamali mediante bioadsorvente opuntia ficus – indica Secclla-Angaraes-Huancavelica, 2022 - Quispealaya, Luis (2023)
The objective was to know the influence of the bioadsorption of opuntia ficus –indica in the acid drainage of Minera Pampamali, 2022; the research was applied, descriptive-correlational level, descriptive-non-experimental method, cross-sectional descriptive design, population comprised of all the Pampamali mine entrances, 8 liters of acid water sample were taken from the main mine entrance; A sample of the opuntia ficus –indica plant was also obtained by simple random sampling; which were transferred to the EPIM-UNH laboratory to submit them to the experimental analysis processes; obtaining as results with the support of the atomic absorption spectrophotometer brand TERMOCIENTIFIC ICE 3000 SERIES AA SPECTROMETER; in 50 ml of acidic water, a concentration of 0.1004 mg/L; then, intervening the opuntia ficus –indica; for a proportion of 100ml of acid water acting with 30g of bioadsorbent, 0.0350mg/L of lead was obtained; among other essays; finally; for 100ml of acid water operating with 80g of bioadsorbent, 0.0096mg/L of lead was reached; meaning that the higher the proportion of bioadsorbent, the lead concentration is significantly reduced; also in comparison to the guidelines of  ECA Supreme Decree No. 023-2009-MINAM, the results are below the maximum permissible limits of lead metal; even in those conditions; the accumulations for tens of years of said polluting metal will generate disorders that are even lethal.